2020
DOI: 10.1097/j.pain.0000000000002087
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory continuous peripheral nerve blocks to treat postamputation phantom limb pain: a multicenter, randomized, quadruple-masked, placebo-controlled clinical trial

Abstract: Supplemental Digital Content is Available in the Text. A 6-day ambulatory continuous peripheral nerve block reduces phantom limb pain and pain-induced physical and emotional dysfunction for at least 4 weeks after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…We subsequently submitted a revised proposal using the reviewer’s preferred smallest meaningful clinical difference of 1.7 points between the treatment and placebo groups , and it was funded. On completing the study, we submitted the manuscript reporting that after 4 weeks, average phantom limb pain intensity was a mean of 3.0 in patients given local anesthetic vs 4.5 in those given placebo (p=0.003) 21. The manuscript was rejected with a reviewer explaining that while our primary endpoint was statistically significant, we had prospectively defined the minimal clinically important difference between treatment groups as 1.7, and we had found a difference of only 1.5 points; demonstrating that while the intervention did, in fact, decrease phantom limb pain, it failed to do so to a clinically relevant degree.…”
Section: Investigator Conundrummentioning
confidence: 99%
See 2 more Smart Citations
“…We subsequently submitted a revised proposal using the reviewer’s preferred smallest meaningful clinical difference of 1.7 points between the treatment and placebo groups , and it was funded. On completing the study, we submitted the manuscript reporting that after 4 weeks, average phantom limb pain intensity was a mean of 3.0 in patients given local anesthetic vs 4.5 in those given placebo (p=0.003) 21. The manuscript was rejected with a reviewer explaining that while our primary endpoint was statistically significant, we had prospectively defined the minimal clinically important difference between treatment groups as 1.7, and we had found a difference of only 1.5 points; demonstrating that while the intervention did, in fact, decrease phantom limb pain, it failed to do so to a clinically relevant degree.…”
Section: Investigator Conundrummentioning
confidence: 99%
“…Gatekeeping permits statistical comparisons of many variables while retaining a study-wide type I error at a 0.05, increasing confidence in all comparisons and aiding interpretation and generalization of the results. In the phantom limb pain study described above, we prospectively specified a statistical gatekeeping strategy which elevated confidence in various secondary outcomes, the first of which was a scale that demonstrated pain’s interference on emotional and physical functioning was a mean of 11 for treated participants, vs 28 for the placebo group (lower scores=less interference; p=0.027) 21. Given that the results of multiple published investigations suggest that a mean group difference of 2 points on this scale indicates patients who are satisfied or improved with treatment,3 our finding of a difference of 17 points suggested a clinically significant improvement in the experimental over placebo treatments; and the results were subsequently published in different journals 21 24…”
Section: Investigatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain basis for these altered perceptions and pain is, as outlined previously, controversial, with the maladaptive plasticity (Flor et al, 1995), including white matter plasticity (Jiang et al, 2015), retained cortical representation (Makin et al, 2013), and peripherally driven (Birbaumer et al, 1997;Ilfeld et al, 2021) theories all having supporting and refuting evidence. It may be the case that these mechanisms are not mutually conclusive.…”
Section: Phantom Limb Painmentioning
confidence: 99%
“…7 A recent randomized controlled trial reported that prolonging a peripheral nerve block using a 6-day continuous perineural local anesthetic infusion extended limb analgesia for at least 1 month. 8 These findings suggest that a peripheral nerve block of extended duration—lasting weeks or months rather than days—may allow prolonged cortical reorganization and provide lasting relief from phantom pain.…”
mentioning
confidence: 98%